HUBUNGAN ANTARA KAPASITAS MENTAL DAN KEPRIBADIAN DASAR BERDASAR PENGUKURAN MMPI-2 DENGAN PERSEPSI, PERILAKU DAN INTENSI INTEGRITAS AKADEMIK MAHASISWA FK UPN âVETERANâ JAKARTA - , HIKMAH MUKTAMIROH; , Prof. Dr. dr. Soenarto Sastrowijoto., Sp THT ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Educational institutions should inculcate the learning of professional behavior as early as possible and conduct evaluation of the implementation, including evaluation of the academic integrity implementation. Academic integrity is the studentâs professional behavior which should receive serious attention. Objective: To determine the academic integrity perception, behavior and intention of students and their relation to mental capacity and basic personality of students based on the MMPI-2 measurements. Methods: This was a non-experimental, quantitative survey on a private medical school in Indonesia by using an academic integrity questionnaire and measurement of MMPI-2. The population was 209 students from level 1, 2 and 3. Results: Descriptions were found about student academic integrity, the relationship between perception, behavior and intentions of academic integrity and the relationship between mental capacity and basic personality based on the measurement of MMPI-2 and the perceptions, attitude and intentions of academic integrity. On mental capacity, a correlation was found between potential performance and perceptions (r = 0.169 and p = 0.014) and academic integrity behavior (r = 0.170 and p = 0.014), between adaptability and the perception of the academic integrity of fellow students (r = 0.149 and p = 0.032), between the psychological constraints and academic integrity behavior score (r = 0.137 and p = 0.049) and between the moral integrity and the perception score of academic integrity (r = - 0.220 and p = 0.001). On the basic personality, there was a correlation between openness to pressure and perceptions of academic integrity of fellow students (r = 0.141 and p = 0.041), as well as between basic personality and perception (r = 0.169 and p = 0.014) and academic integrity behavior (r = 0.154 and p = 0.026). Conclusion: There is a correlation to the number of mental capacity variables based on MMPI-2 with perception and academic integrity behavior as well as correlations of basic personality based on MMPI-2 to perception and academic integrity behavior